Age-dependent increase of magnesium in the cerebral arteries of Thai - Pasuk Mahakkanukrauh (2018)
To elucidate compositional changes of the cerebral arteries with aging, the authors investigated age-related changes of elements in the cerebral arteries by inductively coupled plasma-atomic emission spectrometry (ICP-AES). After an ordinary dissection by medical students at Chiang Mai University was finished, the anterior, middle, and posterior cerebral arteries and the anterior and posterior communicating arteries were resected from the subjects. The subjects consisted of six men and seven women, ranging in age from 34 to 86 yr. The element content was determined by ICP-AES. It was found that the Mg content increased progressively with aging in all of the anterior, middle, and posterior cerebral arteries, but the Ca and P content did not increase significantly with aging in the anterior, middle, and posterior cerebral arteries, with the one exception being that the P content increased significantly in the posterior cerebral arteries with aging. The average content of Ca was higher in the order of the anterior communicating, anterior cerebral, posterior communicating, posterior cerebral, and middle cerebral arteries. © Copyright 2006 by Humana Press Inc. All rights of any nature, whatsoever, reserved.